Jewish minority in the Principality of Bulgaria 1879-1885. Selected problems) - Rusin, Bartłomiej (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article describes the situation of the Jewish minority after establishing the Principality of Bulgaria in 1879. The situation of the Jewish minority and other ethnic and religious groups in the country was heavily dependent on the authorities and different governments aiming at the achievement of the national ideals of Bulgaria – the creation of an ethically solid and territorially united state in the Balkans. These goals influenced the Bulgarian policy towards Jewish and other minorities in the country, especially between 1882-1883 and 1884-1886, when pro-Russian politicians run the government. The Jews in the Principality worked mostly as small merchants and craftsmen, so even though they were considered to be wealthy their situation did not differ from the situation of the Bulgarian population of the country. Generally, the minority was deprived of the possibility of achieving high official and administration posts, as well as high military ranks in the army, even after the participation of the Jews in the Serbo-Bulgarian war in 1885. The education and the level of development of the Jewish culture in the country were also very low. Jewish schools were financially subsidized by international organisations, especially the Alliance Israelite Universelle, but the local communities still lacked money for teachers and proper buildings. Jewish theatres and newspapers were also underfunded, that is why the first Jewish newspaper appeared in the country only in 1893. In conclusion, therefore, it seems that the situation of the Jews in the Principality of Bulgaria was not particularly bad, especially when we take into consideration the level of anti-Semitism in neighbouring Romania. The Jews were satisfied with the conditions of living in Bulgaria, and they supported the national goals of the country, such as the unification of the Principality with the province of Eastern Roumelia in 1885.